Effect of Blast-Furnace Slag Replacement Ratio and Curing Method on Pore Structure Change after Carbonation on Cement Paste - Kim, Junho (Materials (Basel), 2020)
The frost damage resistance of blast-furnace slag (BFS) cement is affected by carbonation. Hence, this study investigates the carbonation properties of pastes incorporating BFS with different replacement ratios, such as 15%, 45%, and 65% by weight, and different curing conditions, including air and carbonation. The BFS replacement ratio properties, determined by the Ca/Si ratio of calcium silicate hydrate in the cement paste sample, were experimentally investigated using mercury intrusion porosimetry, X-ray diffraction, and thermal analysis. The experimental investigation of the pore structure revealed that total porosity decreased after carbonation. In addition, the porosity decreased at a higher rate as the BFS replacement rate increased. Results obtained from this study show that the chemical change led to the higher replacement rate of BFS, which produced a higher amount of vaterite. In addition, the lower the Ca/Si ratio, the higher the amount of calcium carbonate originating from calcium silicate hydrate rather than from calcium hydroxide. As a result of the pore structure change, the number of ink-bottle pores was remarkably reduced by carbonation. Comparing the pore structure change in air-cured and carbonation test specimens, it was found that as the replacement rate of BFS increased, the number of pores with a diameter of 100 nm or more also increased. The higher the replacement rate of BFS, the higher the amount of calcium carbonate produced compared with the amount of calcium hydroxide produced during water curing. Due to the generation of calcium carbonate and the change in pores, the overall number of pores decreased as the amount of calcium carbonate increased.